Mask Mandates Save Lives - Hansen, Niels-Jakob (IMF Working Papers; Working Paper, 2021)
We quantify the effect of mask mandates in the United States. Our regression discontinuity design exploits county-level variation in COVID-19 cases, hospital admissions, and deaths across the border between states with and without mandates. We find a significant and substantial effect-mask mandates reduced new weekly COVID-19 cases, hospital admissions, and deaths by 55, 11 and 0.7 per 100,000 inhabitants on average. Crucially, we find that the effect of mask mandates depends on the attitudes toward mask wearing at the county level, with larger effects in counties more positively inclined towards mask wearing. Our results imply that mandates saved 87,000 lives through December 19, 2020, while a nationwide mandate could have saved 58,000 additional lives. These large effects suggest that mask mandates are a crucial tool to counter pandemics, particularly if accepted widely by the population. Our results are thus also relevant for countries who will not be able to immunize large swaths of their population in the short term.